The impact of aircraft noise on residents residing in the vicinity of Subang Airport - Muhammad Anas Zaki,; Janmaizatulriah Jani,; Shamila Azman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Noise pollution is a prevalent issue in Malaysia, and this investigation focuses on Subang Airport to assess its impact on nearby communities and explore potential mitigation strategies. Given its proximity to densely populated areas, residents express significant apprehension about the noise generated by the airport. The research methodology involves an in-depth examination of aviation noise literatures, the utilization of noise monitoring equipment (sound level meter) for data collection and an analysis of community questionnaires to gauge public perceptions of noise effects. On-site measurements were conducted at seven locations (P1-P7) around the airport, representing varying distances from the noise source over a two-week period. The daily average noise levels range from 40-65 dB(A), which exceed the WHO’s recommended maximum indoor noise level of 35 dB(A) and the suggested maximum noise level for outdoor environments of 55 dB(A). Nevertheless, these averages remain below the permissible exposure limit of 90 dB(A). The study’s significance is further assessed through questionnaire analysis, utilizing Statistical Package for the Social Sciences (SPSS) version 28. Of the 193 respondents (71.7%), the majority identify aircraft noise as a significant source of disruption, with 36.4% attributing major annoyance to traffic noise, 25.7% to industrial noise, and 9.7% to construction-related noise. Respondents collectively emphasize the importance of raising awareness about noise pollution dangers within society and underscore the government’s role in mitigating noise pollution